Effect of Stand-Alone and Combined Ultraviolet and Ultrasound Treatments on Physicochemical and Microbial Characteristics of Pomegranate Juice - Alabdali, Tareq A. M.; Icyer, Necattin Cihat; Ozkaya, Gulsum Ucak; Durak, Muhammed Zeki (MDPI, 2020)
Featured Application This paper features the design of modern pasteurization methods based on two combined non-thermal pasteurization methods. This combined method can be used as an alternative to the conventional thermal pasteurization method as it protects the nutrient content better. The objective of this study was to determine the combined usage possibilities of ultraviolet (UV) and ultrasonic (US) processes in the pasteurization of pomegranate juice. For this purpose, UV, US, and combined UV+US pasteurization of pomegranate juice were optimized using experimental designs, such as the Central Composite Design (CCD) and Factorial Design (FD), and compared with the conventional pasteurization process. Total phenolic content (TPC), color a*, water-soluble dry matter (degrees Brix), turbidity, anthocyanin, DPPH, HPLC TPC, and yeast and mold count were used as quality parameters during all of the processes. The results showed that the application of 50 degrees C, 3.5 L/min flow rate and 5.1 mW/cm2 UV dose, and 10 min US (200 Watt) together reduced the microbial population below the detection limits. The integration of UV+US processes into the pasteurization process could limit microbial activity at lower temperatures and times than the conventional pasteurization process, thus preserving the existing bioactive compounds.
Keywords: pasteurization; pomegranate juice; ultrasound; ultraviolet; optimization; experimental design; PULSED ELECTRIC-FIELDS; SACCHAROMYCES-CEREVISIAE; ESCHERICHIA-COLI; ANTIOXIDANT ACTIVITY; QUALITY PARAMETERS; INACTIVATION; SONICATION; ORANGE; MICROORGANISMS; IRRADIATION; Chemistry; Engineering; Materials Science; Physics